(untitled) (International conference on multidisciplinary science, 2024)
Currently, the treatment of combined burns of the esophagus and stomach continues to be an urgent problem of thoracoabdominal surgery. This is due to the presence of not one, but two levels of obstruction of the digestive tract – esophagus and stomach, which leads to a sharp violation of the alimentary status of patients [1]. The frequency of combined burns of the esophagus and stomach according to various authors ranges from 15 to 53% [2].